Aldehyde dehydrogenase 1 (ALDH1) expression in serrated colonic polyps - Shyshkin, M. A.; Khrystenko, T. O.; Шишкін, Максим Андрійович; Христенко, Тетяна Олексіївна (My University, 2020)
Abstract.Introduction. Immunohistochemical prognostic markers are promising direction for a search. The purpose of the study was analyze ALDH1 immunohistochemical expression in different histological types of serrated polyps of the distal colon. Materials and methods. Histopathological and IHC studies of 30 serrated polyps were conducted. IHC study was carried out using antibodies against ALDH1. Results of IHC reactions were estimated by photo digital morphometry and were expressed in immunostained cells relative area (%). Results. Hyperplastic polyps are characterized by the median of ALDH1+ stromal cells relative area equal to 15,08 (11,12;21,46) % and the median of ALDH1+ epitheliocytes relative area equal to 18,28 (10,14;26,15) %. The basal-middle pattern of ALDH1+ cells distribution was revealed. Traditional serrated adenomas are characterized by the median of ALDH1+ stromal cells relative area equal to 25,63 (18,26;30,42) % and the median of ALDH1+ epitheliocytes relative area equal to 22,13 (17,22;36,05) %. The upper-middle pattern of ALDH1+ cells distribution was revealed. Sessile serrated adenomas are characterized by the median of ALDH1+ stromal cells relative area equal to 23,15 (17,21;29,14) % and the median of ALDH1+ epitheliocytes relative area equal to 20,56 (15,25;26,94) % in these polyps. The basal-middle pattern of ALDH1+ cells distribution was revealed. Conclusions. Number of ALDH1+ stromal cells is significantly higher in traditional serrated adenomas and sessile serrated adenomas comparing to number of those in hyperplastic polyps.
Keywords: Intestinal neoplasms; Polyps; Stem Cells; Aldehyde Dehydrogenase 1